Effect of ghrelin peripheral administration on growth performance, carcass quality, and selected serum parameters in broiler chickens - AGHDAM SHAHRYAR, H.; LOTFI, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
The aim of present study was to investigate the short-term and long-term effect of the peripheral administration of ghrelin on the growth performance (feed intake, weight gain, and feed conversion ratio), carcass quality, and selected serum biochemical (glucose, total cholesterol, triglyceride, and total protein) and hormonal (T3, T4, and corticostrone) indices in broiler chickens. 240 one-day-old broiler chickens were selected, and allocated into three treatment groups (control and two experimental groups). On day-21 of the rearing period, ghrelin was peripherally administrated to three experimental groups. The control group contained birds without any administration of peptide or solution, groups G50 and G100; included birds with Ip-injection of 50 and 100 (ng/100g BW) ghrelin peptide, respectively. The peripheral administration of exogenous ghrelin did not affect feed intake, body weight gain (BWG), feed conversion ratio (FCR) and carcass characteristics in broiler chickens. In short-term samples taken 12h after ghrelin infusion, the glucose level was increased in ghrelin-treated groups (162 and 151 mg/dl in G50 and G100 compared with 117 mg/dl in control; P< 0.01) and there were significant declines for TC, triglyceride, and TP in the ghrelin-treated groups (G50 and G100) compared with the control. In addition, long-term glucose level has a greater value in G50 and G100 (182 and 200.66 mg/dl) compared with control (133.60 mg/dl) group (P< 0.01). A significant decline was also observed for TC and triglyceride content in the ghrelin-treated groups (P<0.05). There was no significant difference among groups for TP in short-term and long-term samples. There was a significant increase for T4 in ghrelin-treated groups (G50 and G100) compared with the control (4.55 and 4.57 ng/ml vs 4.20 ng/ml respectively; P< 0.05) in long-term samples. In conclusion, the peripheral administration of ghrelin in broiler chickens, during the commercial rearing period did not affect the overall growth performance, carcass quality and feed conversion ratio. The infusion of exogenous ghrelin may increase the levels of serum glucose, decrease total cholesterol and triglyceride, and T4 levels are increased in the long-term (and not in the short-term or 12h after administration).